2024
DOI: 10.3390/ijms25063152
|View full text |Cite
|
Sign up to set email alerts
|

Selective Removal of Chlorophyll and Isolation of Lutein from Plant Extracts Using Magnetic Solid Phase Extraction with Iron Oxide Nanoparticles

Jolanta Flieger,
Natalia Żuk,
Sylwia Pasieczna-Patkowska
et al.

Abstract: In recent years, there has been a growing interest in plant pigments as readily available nutraceuticals. Photosynthetic pigments, specifically chlorophylls and carotenoids, renowned for their non-toxic antioxidant properties, are increasingly finding applications beyond their health-promoting attributes. Consequently, there is an ongoing need for cost-effective methods of isolation. This study employs a co-precipitation method to synthesize magnetic iron oxide nanoparticles. Scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…In our previous work, IONPs were characterized by scanning electron microscopy (SEM), energy dispersive spectrometry (EDS) analysis, X-ray photoelectron spectroscopy (XPS), as well as the Brunauer-Emmett-Teller (BET) and the DLS technique [57,58]. It has been found that IONPs obtained by co-precipitation belong to the mesoporous materials with a surface area (BET) of 151.4 m 2 g −1 , spherical shape, size ranging from 80 to 140 nm, and the presence of hydrous iron oxide FeO(OH) on the surface.…”
Section: Characteristics Of Ionpsmentioning
confidence: 99%
“…In our previous work, IONPs were characterized by scanning electron microscopy (SEM), energy dispersive spectrometry (EDS) analysis, X-ray photoelectron spectroscopy (XPS), as well as the Brunauer-Emmett-Teller (BET) and the DLS technique [57,58]. It has been found that IONPs obtained by co-precipitation belong to the mesoporous materials with a surface area (BET) of 151.4 m 2 g −1 , spherical shape, size ranging from 80 to 140 nm, and the presence of hydrous iron oxide FeO(OH) on the surface.…”
Section: Characteristics Of Ionpsmentioning
confidence: 99%